Sulawesi’s Local Culture on Puya ke Puya and Natisha Persembahan Terakhir Novel: Simulacra Process - Rizky Amelya Furqan; Selfi Mahat Putri; Armini Arbain (Balai Bahasa Kalimantan Tengah, 2023)
The influence of developments over time has caused traditions and culture in society to begin to be marginalized because they are considered unreasonable or pre-logical. However, currently many parties are starting to revive the tradition, including the government through tourism and involving writers. Apart from that, writers also express traditions through literary works. This can be seen in the novels Puya ke Puya and Natisha Persembahan Terakhir. The traditions described are people's beliefs about the rambu solo and parakang ceremonies. However, the traditions depicted have been influenced by developments over time so that the traditions depicted are no longer traditions that are believed to be considered sacred like previous societies. Therefore, we can see the depiction of the existence of a tradition through a literary work. The research method used is the literary anthropology approach which discusses the relationship between literature, anthropology and culture. This research aims to see how traditions and culture exist in literary works. The result of this research is that there is a simulakra process of Sulawesi culture in the literary works of the two authors. Apart from that, there is criticism conveyed by the author towards the culture that develops through the response of society as depicted in the characters. Thus, it can be concluded that the culture presented in literary works through the simulakra process does not just introduce culture, but also criticizes society's response to cultural developments. Abstrak Pengaruh perkembangan zaman menyebabkan tradisi dan budaya yang ada di dalam masyarakat mulai dimarginalkan karena dianggap tidak masuk di akal atau bersifat pralogis. Namun, saat ini banyak pihak mulai menyuarakan kembali tradisi, di antaranya pemerintah melalui pariwisata dengan melibatkan sastrawan. Selain itu, sastrawan juga menyuarakan tradisi melalui karya sastra. Hal itu terlihat dalam novel Puya ke Puya dan Natisha Persembahan Terakhir. Tradisi yang digambarkan adalah kepercayaan masyarakat tentang upacara rambu solo dan parakang. Namun, tradisi yang digambarkan telah dipengaruhi oleh perkembangan zaman sehingga bukan lagi merupakan tradisi yang dipercaya dan dianggap sakral seperti anggapan masyarakat sebelumnya. Oleh karena itu, dapat dilihat penggambaran eksistensi sebuah tradisi melalui sebuah karya sastra. Metode penelitian yang digunakan adalah pendekatan antropologi sastra yang membahas keterkaitan sastra, antropologi, dan budaya. Penelitian ini bertujuan melihat bagaimana tradisi dan budaya yang ada dalam karya sastra. Hasil penelitian menunjukkan adanya proses simulakra kebudayaan Sulawesi dalam karya sastra kedua pengarang. Selain itu, terdapat kritik yang disampaikan pengarang terhadap kebudayaan yang berkembang melalui respons masyarakat yang tergambar dalam tokoh. Dengan demikian, dapat disimpulkan bahwa kebudayaan yang dihadirkan dalam karya sastra melalui proses simulakra tidak sekadar memperkenalkan kebudayaan, tetapi juga mengkritisi respons masyarakat terhadap perkembangan kebudayaan tersebut.